2018
DOI: 10.3389/fimmu.2018.01155
|View full text |Cite
|
Sign up to set email alerts
|

The Interleukin-20 Cytokine Family in Liver Disease

Abstract: The three main causes of inflammation and chronic injury in the liver are viral hepatitis, alcohol consumption, and non-alcoholic steatohepatitis, all of which can lead to liver fibrosis, cirrhosis, and hepatocellular carcinoma, which in turn may prompt the need for liver transplant. The interleukin (IL)-20 is a subfamily part of the IL-10 family of cytokines that helps the liver respond to damage and disease, they participate in the control of tissue homeostasis, and in the immunological responses developed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 113 publications
0
18
0
Order By: Relevance
“…A recent review has summarized the functions of IL-20 family cytokines in liver diseases 31 . IL-24 was suggested to function as a protective cytokine during liver inflammation through binding to its corresponding receptors.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review has summarized the functions of IL-20 family cytokines in liver diseases 31 . IL-24 was suggested to function as a protective cytokine during liver inflammation through binding to its corresponding receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, IL-22 has several metabolic benefits, as it decreases chronic inflammation and regulates lipid metabolism in liver and adipose tissues (4,5). In mice, IL-22 elicits hepatoprotective properties via the activation of STAT3 (3,5,21); STAT3 downregulates the expression of lipogenic genes-and consequently reduces fat accumulation-and upregulates the expression of antiapoptotic genes, including reg3. Because the IL-22/STAT3/reg3 axis exists in the intestine (21), it is plausible that IL-22 upregulates REG3␤ and REG3␥ in jejunum via STAT3.…”
Section: Discussionmentioning
confidence: 99%
“…As of today, behavioral changes are considered the main driver to revert metabolic syndrome, but medical intervention strategies are considered the first line of treatment (2). In both nonalcoholic and alcoholic liver disease models, interleukin-20 (IL-20) family cytokines reduce liver injury and inflammation (3). For example, interleukin-22 (IL-22), a member of the IL-20 subfamily, controls lipid metabolism in the liver via activation of the STAT3 signaling pathway and, consequently, reduces fatty liver disease (4).…”
mentioning
confidence: 99%
“…Interleukin-22 (IL-22), as one member of IL-10 cytokine family produced by T-helper (Th)17, Th22, natural killer (NK) cells, is involved in inflammatory reaction 3 , 4 . Extensive evidences indicated that IL-22 plays a protective role in epithelial tissues regeneration in response to infection 5 7 .…”
Section: Introductionmentioning
confidence: 99%